Association Between Vitamin A and D Status and the Risk of COVID-19 in the Elderly Population: A Single-Center Experience - Li T; Cui X; Li X; Yang J; Wang H; Yang J; Jin Z (Journal of Inflammation Research)
Tiewei Li,1,2,* Xudong Cui,2,* Xiaojuan Li,1 Jingping Yang,2 Hongyan Wang,2 Junmei Yang,1 Zhipeng Jin1 1Department of Clinical Laboratory, Children’s Hospital Affiliated to Zhengzhou University, Zhengzhou Key Laboratory of Children’s Infection and Immunity, Zhengzhou, People’s Republic of China; 2Respiratory and Critical Care Medicine Department, Inner Mongolia Baogang Hospital, The Third Affiliated Hospital of Inner Mongolia Medical University, Baotou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingping Yang, Email yangron@sina.com Junmei Yang, Email yangjunmei7683@163.comBackground: Studies have confirmed that vitamins A and D are related to the coronavirus disease 2019 (COVID-19). However, little research has reported the relationship between vitamin A and D nutrition status and COVID-19 in the elderly population in China. Thus, the aim of this study was to explore the association between vitamin A and D status and the risk of COVID-19 in the elderly population.Methods: From April 1st to September 20th, 2023, 32 COVID-19 patients who tested positive for severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection through polymerase chain reaction (PCR) were enrolled in this study. During the same period, 30 elderly individuals undergoing health checkups were enrolled as the control group. Clinical and laboratory data were obtained via electronic medical records. Vitamin A and D levels were detected using ultra-performance liquid chromatography-tandem mass spectrometry. Vitamin A deficiency is a retinol below 30 ng/mL, and vitamin D deficiency is a 25(OH)D below 20 ng/mL. Multivariate logistic regression analysis was used to assess the relationship between vitamin A and D levels, nutritional status, and the risk of COVID-19. Statistical analysis was performed using SPSS 24.0 (SPSS Inc. Chicago, Illinois).Results: Compared with the subjects in the control group, COVID-19 patients had lower levels of vitamins A and D. Further analysis showed that the deficiency rate of vitamins A and D in patients with COVID-19 was higher than those in the control group. Correlation analysis revealed that vitamins A and D significantly negatively correlated with respiratory rate, neutrophil counts and positively correlated with lymphocyte count. Multivariate logistic regression analysis showed that vitamins A and D were the independent risk factors of CIVID-19.Conclusion: Vitamins A and D were significantly lower in COVID-19 patients, and lower vitamins A and D were independently linked with a high risk of COVID-19, according to this single-center analysis.Keywords: COVID-19, vitamin A, vitamin D, elderly population